Children’s Motor Skills Development After Puzzle Play Therapy - Wahyuni, Eko Sari; Solikhah, Fitriana Kurniasari; Septyasih, Rossyana; Prastiwi, Swito (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2025)
Development at preschool age is a basic stage that influences subsequent development, at this time children often experience delays in fine motor development, the impact that often occurs is a lack of stimulation so that children experience obstacles in the learning process at school. One game that improves fine motor development is puzzles. The aim of this research is to identify fine motor development after being given a puzzle game. This research uses a descriptive observational case study on 2 subjects using a modified KPSP observation sheet. The research results before being given the puzzle subject 1 were moderate (10) subject 2 was poor (8) after being given the puzzle both subjects were good (21) and (19). It is recommended that both subjects optimize puzzle games to improve their fine motor development. For future researchers, it is recommended to condition puzzle games simultaneously and not to stimulate separately and it is recommended to involve parents and teachers in conducting research.